Parent Perspective on Care Coordination Services for Their Child with Medical Complexity - Rhonda G. Cady; John L. Belew (MDPI AG, 2017)
The overarching goal of care coordination is communication and co-management across settings. Children with medical complexity require care from multiple services and providers, and the many benefits of care coordination on health and patient experience outcomes have been documented. Despite these findings, parents still report their greatest challenge is communication gaps. When this occurs, parents assume responsibility for aggregating and sharing health information across providers and settings. A new primary-specialty care coordination partnership model for children with medical complexity works to address these challenges and bridge communication gaps. During the first year of the new partnership, parents participated in focus groups to better understand how they perceive communication and collaboration between the providers and services delivering care for their medically complex child. Our findings from these sessions reflect the current literature and highlight additional challenges of rural families, as seen from the perspective of the parents. We found that parents appreciate when professional care coordination is provided, but this is often the exception and not the norm. Additionally, parents feel that the local health system's inability to care for their medically complex child results in unnecessary trips to urban-based specialty care. These gaps require a system-level approach to care coordination and, consequently, new paradigms for delivery are urgently needed.